Role of Selective Estrogen Receptor Modulators in Menopause : A Monocentric Hospital Based Qualitative Appraisal - Mishra, Dr. Rishu Y.; K. Jha, Dr. Rajesh; B. Aglawe, Dr. Priyanka; M. Sakore, Kamini; S. Shrivastava, Dr. Deepti; Mishra, Dr. Vedprakash (International Journal of Innovative Research in Medical Science, 2018)
Menopause transition is experienced by 1.5 million women each year and often involves troublesome symptoms including vasomotor symptoms, vaginal dryness, fatigue, and joint pain. Menopausal hormone therapy has been available for over half a century to provide relief from vasomotor symptoms, osteoporosis and symptoms of urogenital atrophy. Recently there has been an interest in a class of compounds known as the selective estrogen receptor modulators (SERMs) that have been found to be effective in treating postmenopausal symptoms. Hence, the present study was aimed to find out the role of SERMs in menopause. This hospital based analytical study was carried out between 1st January 2016 to 31st March 2018 in OBGY Department of A.V.B. Rural Hospital on 332 women of menopausal age group belonging to rural vidarbha region. The data were collected from in-depth interview of unit heads,professors,associate professors,assistant professors, Junior residents as well as patients in A.V.B. Rural Hospital, Wardha. Menopausal women were categorised in Group I (6th Decade :50 - 59 Years), Group II (7th Decade :60 - 69 Years) and Group III (8th Decade: 70 - 79 Years).The presenting complaints were bone and joint pain(56.01%,26.08%, 19.07% in grade I,II, III), burning micturition( 24.17%,23.60%,16.66% in grade I,II, III, hot flashes( 67.06%,31.00%,26.37 in grade I,II, III), vaginal dryness (21.02%,38.16%,39.11% in grade I,II, III) and uterine prolapse(11.54%,14.16%,16.66% in grade I,II, III). Drug therapy in the form of symptomatic treatment (OCPs) and surgical treatment was given to the patients. SERMs were not given to any patient due to difficulty in keeping follow up and SERMs associated severe adverse effects. Also these patients belong to rural area and for them it is not possible to bear high cost of this drugs. Further investigations and studies are required to help clarify the relative benefits/risks of novel SERMs in development within specific indications and in patient‐specific management in the field of postmenopausal health.